PENGARUH MEDIA SANDPAPER LETTER TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK USIA 5-6 TAHUN DI TK VIZAHRI - Elviyana Barus; Aminda Tri Handayani (STKIP Subang, 2024)
Beginning reading skills are the simplest reading skills. Beginning reading skills include several activities such as recognizing letters and words, connecting them with sounds or voicing letters, syllables, and sentences formed in writing into oral form. The ability to read at the beginning is the basic skill of the child, if the basic ability is not strong then the period at the next stage the children have difficulty. This early reading ability is a provision for children to enter the next level. Researchers provide sandpaper letters as a learning medium that can help overcome the ability of beginning reading in children at Tk Vizahri. Sandpaper letter is one of the learning media used in the Montessori method as an exercise to build the muscle mechanism needed for the ability to hold and use stationery then the child's finger that has been trained through the activity of feeling the shapes of letters to complement the child's visual knowledge of letters. Based on the results of the study, the use of sandpaper letter media can be used to improve the initial reading skills of group B children at Vizahri Kindergarten which is proven through the normality test through one-sample Kolmogorov Smirnov with the sig value obtained. Smirnov Test > alpha level = 0.05. The data obtained is 0.725> 0.05 and the hypothesis test is obtained with the value of Thitung = 1.934> 1.720, and because dk = (n-1) = 19 and the real level ɑ = 0.05 so it can be concluded that Thitung> Ttabel (1.934) (1.720) thus the hypothesis H0 is rejected and H1 is accepted. So it can be stated that there is a significant effect of using sandpaper letter media on the ability to read beginning in children 5-6 years in Vizahri Kindergarten